2020
DOI: 10.1162/edfp_a_00282
|View full text |Cite
|
Sign up to set email alerts
|

Does School Finance Reform Reduce the Race Gap in School Funding?

Abstract: This paper offers new evidence on the impacts of school finance reforms (SFRs) precipitated by school finance litigation, exploring the extent to which the impact of SFR differs by district racial composition. Using difference-in-differences and event study models with a series of district and year (or state-by-year) fixed effects, and a sixteen-year panel of over 10,000 school districts, my analyses exploit variation in funding across school districts, and timing of school finance court orders across states, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Insofar as better facilities promote student learning, achievement effects would continue to grow until several years after the last project is complete, potentially decades after the initial policy change. We thus emphasize the phase-in coefficient from equation (2) as the primary measure of SFR effects on test scores. Figure 6 presents our event-study analysis of the slope of achievement with respect to district income.…”
Section: Finance Reforms and District-level Student Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…Insofar as better facilities promote student learning, achievement effects would continue to grow until several years after the last project is complete, potentially decades after the initial policy change. We thus emphasize the phase-in coefficient from equation (2) as the primary measure of SFR effects on test scores. Figure 6 presents our event-study analysis of the slope of achievement with respect to district income.…”
Section: Finance Reforms and District-level Student Achievementmentioning
confidence: 99%
“…district-level mean household income distribution). 2 Between 1990 and 2012, real per pupil revenues rose by roughly 30 percent in the highest income districts, and by over 50 percent in the lowest income districts. Thus, while low-income districts collected about 20 percent less than high-income districts in 1990, they have been in rough parity since around 2001.…”
mentioning
confidence: 99%
“…The pertinent argument on public education discourse is that students who enjoy public education do not pay for academic services? In responding to that, in the United States of America, education is visualized as one of the major sources of revenue for the government (Rothbart, 2020), which invariably cannot be fully funded by the government.…”
Section: Discussionmentioning
confidence: 99%
“…In other states, they were the result of legislative activity alone (Lafortune et al, 2018). Studies of these reforms have found that they narrowed racial funding gaps (Rothbart, 2020), improved graduation rates (Candelaria & Shores, 2019;Jackson et al, 2016), increased standardized test scores (Lafortune et al, 2018), and even positively impacted long-term outcomes such as future adult earnings (Jackson et al, 2016).…”
Section: State Policymakers and School Finance Reformmentioning
confidence: 99%
“…Increases in state education aid to school districts can help address these disparities. One recent study found that changes to state education funding systems precipitated by school finance litigation between 1996 and 2011 helped reduce racial disparities in funding (Rothbart, 2020). Several national studies have found that court-ordered school finance reforms have positively impacted a range of educational outcomes as well, including graduation rates (Candelaria & Shores, 2019;Jackson et al, 2016), standardized test scores (Lafortune et al, 2018), and future adult earnings (Jackson et al, 2016).…”
mentioning
confidence: 99%